Respiratory Tract Manifestations of Inflammatory Bowel Disease. Issue 4 (25th May 2020) - Kröner, Paul T; Lee, Augustine; Farraye, Francis A
Abstract: Inflammatory bowel disease can manifest in many extraintestinal organ systems. The most frequently involved extraintestinal locations include the mucocutaneous, hepatobiliary, and ocular organ systems. The respiratory tract is less commonly involved and is therefore frequently overlooked. Consequently, it is believed that involvement of the respiratory tract in patients with inflammatory bowel disease is underreported. The pathogenesis is thought to be multifactorial, involving the common embryologic origin shared by the respiratory and luminal digestive tract, molecular mimicry, and immunologic interactions leading to immune-complex deposition in affected tissue. The spectrum of manifestations of the respiratory tract related to inflammatory bowel disease is broad. It not only includes direct involvement of the respiratory tract (ie, airways, interstitium, and pleura) but also can result as a consequence of systemic involvement such as in thromboembolic events. In addition, it may also be related to other conditions that affect the respiratory tract such as sarcoidosis and alpha-1 antitrypsin deficiency. Though some conditions related to respiratory tract involvement might be subclinical, others may have life-threatening consequences. It is critical to approach patients with suspected inflammatory bowel disease–related respiratory tract involvement in concert with pulmonology, infectious diseases, and any other pertinent experts, as treatments may require a multidisciplinary overlap of measures. Therefore, it is of paramount importance for the clinician to be aware of the array of respiratory tract manifestations of patients with inflammatory bowel disease, in addition to the possible spectrum of therapeutic measures.